2013
DOI: 10.1017/s1368980012005472
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural patterns of protective and risk factors for non-communicable diseases in Brazil

Abstract: Objective: To identify behavioural patterns of protective and risk factors for non-communicable diseases (NCD) and to explore the association between these patterns and sociodemographic characteristics. Design: Principal component analysis was used to identify behavioural patterns from a list of twelve protective and risk factors for NCD. Linear regression was used to explore the association between the patterns and sociodemographic characteristics. Setting: Participants from the Brazilian Surveillance System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
3
24
0
4
Order By: Relevance
“…That investigation showed results similar to those of this present study, where it was found that the behavioral pattern considered risk was defined by smoking, excessive alcohol consumption and regular intake of meat with visible fat (31). Therefore, strategies to control the increase in the prevalence of such risk factors in the population may be directed to these three factors, which have a tendency to aggregate.…”
Section: Behavioral Patterns That Increase or Decrease Risk Of Abdomisupporting
confidence: 89%
See 2 more Smart Citations
“…That investigation showed results similar to those of this present study, where it was found that the behavioral pattern considered risk was defined by smoking, excessive alcohol consumption and regular intake of meat with visible fat (31). Therefore, strategies to control the increase in the prevalence of such risk factors in the population may be directed to these three factors, which have a tendency to aggregate.…”
Section: Behavioral Patterns That Increase or Decrease Risk Of Abdomisupporting
confidence: 89%
“…Smoking was categorized into smokers, former smokers and non-smokers, regardless of the frequency and intensity of using tobacco (31). The abusive consumption of alcohol was considered as present when the intake of at least five shots in a single sitting occurred, based on the reference of the past 30 days for men and at least four for women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, violent behaviour, drug use and smoking are less socially acceptable behaviours among adolescents,9 and were captured by the problem-behaviour pattern, while the health-compromising diet and sedentary behaviours pattern brought together behaviours that represent harm to health but are not seen as unacceptable either by students or society, such as unhealthy food consumption and sedentary behaviour 9. Among Brazilian adults, drinking alcohol and smoking were found as part of a risky lifestyle pattern, together with lack of physical activity and unhealthy diet intake,8 in contrast with our findings among adolescents. Among adults, drinking alcohol and smoking are common and socially accepted, while they are contesting or rule-breaking behaviours among adolescents 9.…”
Section: Discussionmentioning
confidence: 99%
“…In the current Brazilian epidemiological and nutritional context, conditions of overweight, obesity and non-transmissible chronic diseases (NTCDs) have been showing continuous progression, even among lower-income classes 5,6 . Therefore, identification and monitoring of the nutritional status of beneficiaries of social assistance programs, such as feeding and nutrition programs, becomes particularly necessary.…”
Section: Introductionmentioning
confidence: 99%